Characterization of magnesium doped lanthanum orthoniobate synthesized by molten salt route. Issue 6 (July 2015) - Mielewczyk-Gryn, A.; Wachowski, S.; Zagórski, K.; Jasiński, P.; Gazda, M.
Abstract: Molten salt synthesis method has been used to prepare the single phase magnesium doped lanthanum orthoniobate. The phase composition has been checked by X-ray diffraction method and the microstructure studies have been performed by scanning electron microscopy. The high temperature properties of the material have been investigated by thermogravimetry and electrochemical impedance spectroscopy. A dependence between sample total conductivity and temperature has been found supporting the thesis that there is strong correlation between apparent activation energy of conductivity and structural phase transition at ~500 °C. It has been also shown that the conductivity of magnesium doped lanthanum orthoniobate synthesized by the molten salt route reaches values of ~1 mS/cm at 720 °C in wet hydrogen.